Jazz as a demonstration of personal freedon in the USA in 1950s presented in the book On The Road by Jack Kerouac - Budinská, Romana (Univerzita Pardubice, 2014)
The aim of this paper is to analyze the influence of jazz in On the Road by Jack Kerouac. The main focus is on identifying jazz as a theme and its effect on characters' lives and, in addition, recognizing whether formal jazz rules were applied in the novel. To a limited extent, the paper deals with basic information about jazz, bebop in particular, and the Beat Generation, with an emphasis on Neal Cassady due to his role in the novel, and Jack Kerouac as a writer and main protagonist of the novel. Kerouac's life and his literary experimentation introduce the topic which is further discussed in the analytical part. To support the analysis, Kerouac's experimentation with spontaneous prose was introduced and its rules were partially applied to support the analysis of form and composition of the novel. Finally, a comparison between the Original Scroll and edited version of On the Road is included.
Jazz jako demonstrace osobní svobody v USA v padesátých letech zobrazené v románu Na cestě od Jacka Kerouaca
Keywords: Kerouac, Jack; jazz; Beat Generation; spontaneous prose; Kerouac, Jack; jazz; Beatová generace; spontánní próza